(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The project aims to enhance voltage-stability and improve power quality in smart grids by using renewable energy sources (RES) and a 31-level inverter. The 31-level inverter uses cascaded H-bridge topology, which allows for high-voltage, high-power applications with reduced harmonic distortion